2018
DOI: 10.1002/pat.4333
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure–dependent wear behavior of thermoplastic polymers in deep sea

Abstract: It is generally acknowledged that wear behavior of approved water-lubricated thermoplastic polymers are not susceptible to hydrostatic pressure in seawater environment.However, in our recent study reported in this letter, it has been shown that the wear behavior of thermoplastic polymers sliding in seawater is strongly dependent on the hydrostatic pressure. The correlation between hydrostatic pressure and wear rates of thermoplastic polymers can be expressed in an identical form of exponential function, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Therefore, polymer materials have great application prospects as friction pair component materials in wading environment. [5][6][7][8] For a tribological system in water environment, its tribological characteristics are affected by many factors. Among them, the water absorption of polymer friction materials is an important factor that must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, polymer materials have great application prospects as friction pair component materials in wading environment. [5][6][7][8] For a tribological system in water environment, its tribological characteristics are affected by many factors. Among them, the water absorption of polymer friction materials is an important factor that must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers and their composite materials are widely used in seals, piston rings, valves, lubricating bearings, and bearing retainers for sea-related equipment, owing to their superior properties [ 7 , 8 ]. In particular, polymers and their composites have proven to be promising seawater-lubricated materials because of their excellent corrosion resistance, low friction, and high wear resistance under seawater lubrication [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on the effects of pressure, running speed, marine environment, and other factors on the tribological properties of polymers [16][17][18]. Liu [13] investigated the relationship between hydrostatic pressure and the wear behavior of thermoplastic polymers sliding in seawater. It was demonstrated that an increase in the hydrostatic pressure increased the wear rate of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Another example can be lip seals, which after mounting on the shaft are deformed and, in this state, interact frictionally with the metal surface (Figure 1c). Sliding elements made of polymeric materials may also be used in modern underwater robots where they are deformed as a result of hydrostatic pressure [3].…”
Section: Introductionmentioning
confidence: 99%